Sobre la distribución e identificación serológica del género Salmonella en Costa Rica - Bolaños, Roger (1958)
In a study of our national literature on Salmonella, completed with our personal observations, we find that 98,9 per cent of the serotypes are included in the first five groups of the Kauffmann and White scheme. These strains originated from surveys carried out on pigs, food handlers, infantile enteritis, appendices, cattle and humans with or without symptomatology of intestinal disturbances. On the basis of this incidence we recommend the somatic and flagellar sera necessary to be able to identify the maximum number of strains of Salmonella in Costa Rica.